Economy-wide implications of biofuel production in Zambia - Faaiqa Hartley; Dirk Ernst van Seventer; Paul Samboko; Channing Arndt (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
It is estimated that biofuel demand in South Africa will increase to 1,550 million litres by 2025 following the introduction of mandatory blending rates in 2014. Land and water constraints, however, limit domestic supply ability. Zambia, due to abundance of land, suitable climate, supportive bioenergy incentives, and geographical proximity, has the potential to meet this increased demand. Using a dynamic recursive computable general equilibrium model, we estimate the macro- and socio-economic impacts of bioethanol production in Zambia under both commercial and smallholder farming models, including and excluding bagasse co-generation. Three feedstock crops are considered: sugarcane, cassava, and sweet sorghum.
Keywords: C68; Q16; Q18; 330; bioenergy; bioethanol; CGE; economy-wide modelling; Zambia